(untitled) (Acta Scientiarum. Biological Sciences, 2013)
Exotic freshwater fish can have deleterious effects on local biodiversity, although these impacts often only become apparent many years after the introduction. Local Ecological Knowledge (LEK) may be a useful source of information in situations where formal technical studies are insufficient, but few works have examined the reliability of information generated through this approach. We examined the reliability of LEK by investigating the impacts of Nile tilapia on fishery stocks in an artificial reservoir in northeastern Brazil. We gathered LEK from 29 experienced fishermen and then confronted this information with official fishery statistics from the same site. Twenty-two fishermen stated that total catch in the Gargalheiras Reservoir had declined over the years, 68% (N=15) of them began fishing before 1976 (the year Nile tilapia was introduced into reservoir). Of those 15 fishermen, 87% (N=13) stated that tilapia has not negatively affected other species, which ran counter to analyses of fishery statistics. Our study suggests that the LEK of fishermen is not a useful source of information concerning the impacts caused by exotic tilapia. However, the LEK added an overfishing hypothesis of the decline in fishery stocks in the Gargalheiras reservoir.